Association Between Exposure to General Versus Regional Anesthesia and Risk of Dementia in Older Adults. Issue 1 (6th October 2020) - Velkers, Clive; Berger, Miles; Gill, Sudeep S.; Eckenhoff, Roderic; Stuart, Heather; Whitehead, Marlo; Austin, Peter C.; Rochon, Paula A.; Seitz, Dallas
Abstract : BACKGROUND/OBJECTIVES: Cognitive changes are commonly observed in older adults following surgical procedures. There are concerns that exposure to general anesthesia (GA) may contribute to an increased risk of Alzheimer's disease. Our study examined the associations between exposure to GA compared with regional anesthesia (RA) administered for elective surgical procedures and the development of dementia. DESIGN: Population‐based propensity matched retrospective cohort study. SETTING: Linked administrative databases were accessed from ICES (formerly called the Institute for Clinical Evaluative Services) in Ontario, Canada. PARTICIPANTS: We included all community‐dwelling individuals aged 66 and older who underwent one of five elective surgical procedures in Ontario, Canada, between April 1, 2007, and March 31, 2011. Individuals with evidence of dementia preceding cohort entry were excluded. Individuals who received GA were matched within surgical procedures to those who received RA on age, sex, cohort entry year, and a propensity score to control for potential confounders. MEASUREMENTS: The baseline characteristics of the study sample were compared before and after matching. Individuals were followed for up to 5 years following cohort entry for the occurrence of dementia using a validated algorithm. Cox proportional hazards analysis was used to determine the hazard ratio (HR) and 95% confidence interval (CI) for the association between anesthetic type and dementia. Subgroup and sensitivity analyses were undertaken. RESULTS: A total of 7, 499 matched pairs were included in the final analysis. Overall, no difference was observed in the risk of being diagnosed with dementia for individuals who received GA when compared with RA (HR = 1.0; 95% CI = .8–1.2). There was also no association between anesthesia and dementia in most subgroup and sensitivity analyses. CONCLUSION: Elective surgery using GA was not associated with an overall elevated risk of dementia when compared with RA. Future studies are required to determine whether surgery is a risk factor for dementia irrespective of anesthetic technique.